Development and Characterization of a PLA Biocomposite reinforced with Date Palm Fibers - Ghanmi, Ines; Slimani, Faouzi; Ghanmi, Samir; Guedri, Mohamed (Engineering, Technology & Applied Science Research, 2024)
Despite the promising potential of bio-composites derived from plant fibers due to their ecological and economic benefits, challenges persist in their preparation, restricting their commercial applications. These challenges are primarily associated with developing suitable methods, acquiring appropriate equipment for treating plant fibers, and addressing the time constraints in preparation. This study aims to contribute to the development and characterization of a new biocomposite and biodegradable material based on natural fibers produced through hot compression. The newly developed biocomposite comprises commercial biodegradable poly-lactic acid (PLA) as a matrix and untreated fiber fabric extracted from date palms as reinforcement. The use of untreated fiber fabric has successfully overcome the preparation difficulties. Experimental results on the new biocomposite reveal the strong adhesion between its fibers and the matrix, emphasizing the significant impact of choosing the right manufacturing conditions on the developed mechanical properties.